2023
DOI: 10.15360/1813-9779-2023-3-46-53
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study of Neuroprotective Properties of Inhaled Argon-Oxygen Mixture in a Photoinduced Ischemic Stroke Model

E. A. Boeva,
D. N. Silachev,
E. I. Yakupova
et al.

Abstract: Acute ischemic stroke is a serious problem for healthcare systems worldwide. Searching for the optimal neuroprotector is a contemporary challenge. Various studies have demonstrated neuroprotective properties of argon in ischemic brain damage models. However, the published data are inconsistent.The aim of the study was to evaluate the effect of 24-hour argon-oxygen mixture (Ar 70%/O₂ 30%) inhalation on the severity of neurological deficit and the extent of brain damage in rats after a photoinduced ischemic stro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…In addition, the mechanisms underlying xenon-induced neuroprotection have been extensively studied [ 23 , 24 ]. For argon, there are far fewer studies [ 22 , 25 , 26 ], and they do not always clearly indicate the presence of protective effects on the brain [ 8 , 9 , 21 , 27 ]. Few studies have demonstrated the neuroprotective potential of neon and krypton [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the mechanisms underlying xenon-induced neuroprotection have been extensively studied [ 23 , 24 ]. For argon, there are far fewer studies [ 22 , 25 , 26 ], and they do not always clearly indicate the presence of protective effects on the brain [ 8 , 9 , 21 , 27 ]. Few studies have demonstrated the neuroprotective potential of neon and krypton [ 24 ].…”
Section: Discussionmentioning
confidence: 99%